E-Commerce beyond the Pandemic Coronavirus: Click and Collect Food Ordering - Hadi Mohamad A.; Athirah Hamzah A.; Ramli R.; Fathullah M. (IOP Publishing Ltd, 2023)
Online platforms have become a focus nowadays as an instrument to help expedite some daily routines such as e-commerce including food ordering, online banking, social networking, and many more. Food ordering through online platforms, for instance, have evolved due to the growing numbers of users of digital platforms, restaurant-goers, and many more. The recent pandemic of coronavirus has changed the scenario of brick-and-mortar businesses while most governments forced to shut down and impose strict regulations of lockdown and social distancing among citizens. Although this situation hit most businesses, statistics have shown there is an increasing amount of E-Commerce spending globally. There has been several commercial systems and studies in the market and literature related to food ordering platforms and processes discussed in the study. However, most systems focusing on order-to-delivery and imposed a higher price for delivery. This study introduces an O2O food ordering concept aiming the takeout customers segment and targeting to optimised orders that can be made in advanced and on-the-go. The concept generates models of a new O2O and distance food ordering for potential E-Commerce implementations. Out of the models, process improvement is analysed and suggest that customers would save time, effort, and able to maintain social distancing among citizens. The models can be generalised to be implemented in various industries and situations, depending on in-depth analysis that would be carried out in future studies. Published under licence by IOP Publishing Ltd.